Integrasi Dakwah dan Ekonomi dalam Literasi Keuangan BAZNAS Indonesia - Muhammad Farhan; Muhammad Yusuf Siddik; Abdul Ghoni; Muqoddam Cholil (Social Science Academic, 2026)
This article examines the integration of da'wah and economics in the social life of Muslim communities through the financial literacy program of BAZNAS Indonesia. The study is based on the view that da'wah is not limited to verbal religious preaching, but also includes social and economic empowerment to reduce poverty, strengthen financial responsibility, and build community welfare. Using a descriptive qualitative method supported by field and library research, this study analyzes interviews with BAZNAS officers and mustahik, documentation, and relevant literature on Islamic economics, zakat, and sharia financial literacy. The findings show that BAZNAS integrates da'wah and economics through spiritual guidance, financial education, productive zakat, business mentoring, and empowerment programs such as Zmart and micro-enterprise assistance. The program encourages mustahik to record income and expenses, separate business capital from household funds, save gradually, avoid usury-based practices, and view economic activity as part of worship and social responsibility. The main challenges include inconsistent beneficiary commitment, unstable income, and external constraints. The program demonstrates that zakat-based financial literacy can become a strategic form of da'wah bi al-hal that strengthens economic independence and social welfare.